1989
DOI: 10.1128/mcb.9.3.1362
|View full text |Cite
|
Sign up to set email alerts
|

Immunological identification of the alternative oxidase of Neurospora crassa mitochondria.

Abstract: Neurospora crassa mitochondria use a branched electron transport system in which one branch is a conventional cytochrome system and the other is an alternative cyanide-resistant, hydroxamic acid-sensitive oxidase that is induced when the cytochrome system is impaired. We used a monoclonal antibody to the alternative oxidase of the higher plant Sauromatum guttatum to identify a similar set of related polypeptides (Mr, 36,500 and 37,000) that was associated with the alternative oxidase activity of N. crassa mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
1
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 13 publications
0
46
1
2
Order By: Relevance
“…The aod-1 gene (4nc285_080 [Table 31]) codes for the Neurospora alternative oxidase (472). Mutant screens also identified the aod-2 gene, which is thought to encode an as-yet-unidentified regulatory factor required for aod-1 expression (72,449). A search of the Neurospora genome revealed a close relative of aod-1.…”
Section: Mitochondrion and Energy Metabolismmentioning
confidence: 99%
“…The aod-1 gene (4nc285_080 [Table 31]) codes for the Neurospora alternative oxidase (472). Mutant screens also identified the aod-2 gene, which is thought to encode an as-yet-unidentified regulatory factor required for aod-1 expression (72,449). A search of the Neurospora genome revealed a close relative of aod-1.…”
Section: Mitochondrion and Energy Metabolismmentioning
confidence: 99%
“…In Trypanosoma brucei, the enzyme is the exclusive terminal oxidase in mitochondria of the bloodstream form of this parasitic protozoan and may be essential for its survival (Helfert et al 2001;Chaudhuri et al 2006). It has been suggested that fungi or animals that encounter inhibitors of complex III or IV in nature may utilize alternative oxidase to escape the effects of these compounds (Lambowitz and Zannoni 1978;Joseph-Horne et al 2001;McDonald and Vanlerberghe 2004).…”
mentioning
confidence: 99%
“…Under normal growth conditions, alternative oxidase is not detectable, but when oxidative phosphorylation is impaired by mutations or inhibitors, expression of the aod-1 gene is induced (Bertrand et al 1983;Tanton et al 2003). In the 1980s, mutant screens revealed that the aod-2 gene was required for expression of aod-1 (Bertrand et al 1983;Lambowitz et al 1989). Additional genes (aod-4, aod-5, aod-6, and aod-7) that may be involved in a signal transduction pathway for alternative oxidase expression in N. crassa have been discovered more recently (Descheneau et al 2005).…”
mentioning
confidence: 99%
“…The protein is not detectable under standard growth conditions. Its expression is strongly induced by mutations or chemicals that inhibit the ETC, and significant regulation occurs at the level of transcription (Lambowitz et al 1989;Li et al 1996;Lorin et al 2001;Affourtit et al 2002;Tanton et al 2003;Descheneau et al 2005;Chae et al 2007a,b). In higher plants, AOX expression depends on developmental signals, stress conditions, and inhibition of the respiratory chain (reviewed in Clifton et al 2006).…”
mentioning
confidence: 99%